2013
DOI: 10.1088/1674-1056/22/11/116805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of buoyancy-driven convection on steady state dendritic growth in a binary alloy

Abstract: The effect of buoyancy-driven convection on the steady state dendritic growth in an undercooled binary alloy is studied. For the case of the moderate modified Grashof number, the uniformly valid asymptotic solution in the entire region of space is obtained by means of the matched asymptotic expansion method. The analytical results show that the buoyancydriven convection has a significant effect on the needle-like interface of dendritic growth. Due to the buoyancy-driven convection, the needle-like interface sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…With Eqs. ( 15), (16), and the interface condition (18), we obtain the leading order approximation solutions for the temperature fields written as…”
Section: Asymptotic Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…With Eqs. ( 15), (16), and the interface condition (18), we obtain the leading order approximation solutions for the temperature fields written as…”
Section: Asymptotic Solutionmentioning
confidence: 99%
“…Buchholz and Engler [8] found that the deformation of the solute layer around the dendrites tips caused by the forced convection makes the columnar dendrites tips incline in the upstream direction. [9,10] In the solidification, the crystal growth will be affected by many factors, such as undercooling, [11] interface kinetics, [12] anisotropic surface tension, [13,14] flow, [15][16][17][18][19] etc. These experiments and numerical simulations deepen the understanding of the crystal growth.…”
Section: Introductionmentioning
confidence: 99%
“…The convective enhancement of impurity supply can increase the amplitude of defects-causing fluctuations and lead to the crystal quality degradation. Chen and Wang et al (2013) investigated the effect of buoyancy-driven convection on the needle-like interface shape of the crystal. Many helpful results from the above research of protein growth indicated that convection can affect the crystal growth rate and quality, except for very low flow rates.…”
Section: Introductionmentioning
confidence: 99%